If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+15-92=(x+2)
We move all terms to the left:
3x+15-92-((x+2))=0
We add all the numbers together, and all the variables
3x-((x+2))-77=0
We calculate terms in parentheses: -((x+2)), so:We get rid of parentheses
(x+2)
We get rid of parentheses
x+2
Back to the equation:
-(x+2)
3x-x-2-77=0
We add all the numbers together, and all the variables
2x-79=0
We move all terms containing x to the left, all other terms to the right
2x=79
x=79/2
x=39+1/2
| 9+10n=69 | | 10-6+10x=2x-12+4x | | 5x+2-2-3x=9+5 | | -1(7x+4x-5)=9-(3x+5) | | -5x-30=7 | | 3/5(35x+15)=2/3(9x-21) | | 3/m+4=9 | | 3(x+1)-2(x+1)=2x+10 | | 0.5(x+20)=2+0.75(x−2) | | 6n=246 | | 8x=4=68 | | 1/6(12x-18)=2x=3 | | 16-4n=12 | | 8x+4=98 | | (5x+16)+90+100+102=180 | | Y=5.2(8-y) | | -2z-0z=-21 | | 6x−35+3x+35=180 | | 5t+5t=6-16 | | m/2+-4=-3 | | 2x+5+3x=4-(x-4) | | 12=3(d-14) | | 3v-(2.34)=9.57 | | 4x-2/3=-6x+1/7 | | 3x-2x+6=22 | | 17=j/13 | | -65-x=-4x+22 | | 6-2k-7=3 | | 3y+5=7y-31 | | Y=-11/2x-29 | | 17=4j+31 | | -90=-5v+5(7v-6) |